2021
DOI: 10.3390/healthcare10010039
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Associations between Medical Expenditure, Perceived Medical Attitude, and Sociodemographics, and Older Adults’ Self-Rated Health in China: Applying the Extreme Gradient Boosting Model

Abstract: Background: although China’s total health expenditure has been dramatically increased so that the country can cope with its aging population, inequalities among individuals in terms of their medical expenditures (relative to their income level) have exacerbated health problems among older adults. This study aims to examine the nonlinear associations between each of medical expenditure, perceived medical attitude, and sociodemographics, and older adults’ self-rated health (SRH); it does so by using data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Our results showed that drinking can reduce medical expenditures: the outpatient expenditure decreased by 11.5% (p = 0.044); inpatient expenditure decreased by 6.8% (p = 0.032); and total medical expenditure decreased by 17.1% (p = 0.040). This finding is consistent with the research conclusion of Song et al (2020) [36]. In addition, the outpatient expenditure, inpatient expenditure, and total medical expenditure of urban residents were all higher than rural residents, and the results were at the significance level of 1%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that drinking can reduce medical expenditures: the outpatient expenditure decreased by 11.5% (p = 0.044); inpatient expenditure decreased by 6.8% (p = 0.032); and total medical expenditure decreased by 17.1% (p = 0.040). This finding is consistent with the research conclusion of Song et al (2020) [36]. In addition, the outpatient expenditure, inpatient expenditure, and total medical expenditure of urban residents were all higher than rural residents, and the results were at the significance level of 1%.…”
Section: Discussionsupporting
confidence: 92%
“…Wang et al (2019) [33], Su et al (2020) [34], and Song et al (2020) [35], respectively, confirmed that physical activity was associated with lower medical expenditure in middle-aged and elderly patients with coronary heart disease, diabetes mellitus, and cardiovascular disease. In addition, Liang et al (2022) [36] used the extreme gradient-boosting model and found physical exercise status to be a robust predictor of self-rated health (SRH) outcomes in older adults, based on the data from the 2018 China Family Panel Studies survey. However, compared with the research in other countries, especially in Europe and the United States, the depth of relevant research and analysis methods in China still needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should pay special attention to examining specific health indicators once the data are available. Nonlinear associations between perceived attitudes toward medical services and health benefits are encouraged to explore findings among different population groups by conducting machine learning and deep learning approaches [ 56 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…LGBM and XGB presented a relative advantage with regard to efficient computation and high accuracy on a wide range of data sets, including those with high dimensionality and categorical features [22][23][24][25]. Both methods required sequential decision tree generation via error combination or level-wise tree growth.…”
Section: Submodels: Lgbm and Xgbmentioning
confidence: 99%